Identification of cis-regulatory mutations generating de novo edges in personalized cancer gene regulatory networks - Zeynep Kalender Atak; Hana Imrichova; Dmitry Svetlichnyy; Gert Hulselmans; Valerie Christiaens; Joke Reumers; Hugo Ceulemans; Stein Aerts (Genome Medicine, 2017)
Abstract The identification of functional non-coding mutations is a key challenge in the field of genomics. Here we introduce μ-cisTarget to filter, annotate and prioritize cis-regulatory mutations based on their putative effect on the underlying “personal” gene regulatory network. We validated μ-cisTarget by re-analyzing the TAL1 and LMO1 enhancer mutations in T-ALL, and the TERT promoter mutation in melanoma. Next, we re-sequenced the full genomes of ten cancer cell lines and used matched transcriptome data and motif discovery to identify master regulators with de novo binding sites that result in the up-regulation of nearby oncogenic drivers. μ-cisTarget is available from http://mucistarget.aertslab.org .